Museomics Clarifies the Classification of Aloidendron (Asphodelaceae), the Iconic African Tree Aloes - Malakasi, Panagiota; Bellot, Sidonie; Dee, Richard; Grace, Olwen M. (Frontiers in Plant Science, 2019)
Arborescent succulent plants are regarded as keystone and indicator species in desert ecosystems due to their large stature and long lifespans. Tree aloes, the genus Aloidendron, are icons of the southern African deserts yet have proved elusive subjects due to the difficulty of obtaining material of known provenance for comparative study. Consequently, evolutionary relationships among representatives of the unusual arborescent life form have remained unclear until now. We used an museomics approach to overcome this challenge. Chloroplast genomes of six Aloidendron species and 12 other members of Asphodelaceae were sequenced from modern living collections and herbarium specimens, including the type specimens of all but two Aloidendron species, the earliest of which was collected 130 years ago. Maximum likelihood trees estimated from full chloroplast genomes and the nuclear ITS region show that Aloidendron sabaeum, from the Arabian Peninsula, is nested within Aloe while the Madagascar endemic Aloestrela suzannae is most closely related to the Somalian Aloidendron eminens. We observed phylogenetic conflicts between the plastid and nuclear topologies, which may be indicative of recurrent hybridization or incomplete lineage sorting events in Aloe and in Aloidendron. Comparing species ecology in the context provided by our phylogeny suggests that habitat preference to either xeric deserts or humid forests/ thickets evolved repeatedly in Aloidendron. Our findings demonstrate the value of botanical collections for the study and classification of taxonomically challenging succulent plants.